(untitled) (Global Journal of Science Frontier Research, 2012)
Cocoa cultivation is a major activity in Ghanaian agriculture supporting the livelihood of over 400,000 farm-families and their dependents. Cocoa marketing centers are farmers’ first point of call to obtain money for their dry cocoa beans. Using survey methods, the study set out to investigate the nature of the relationship between farmers and purchasing clerks in 20 cocoa communities in the western, Ashanti and Volta regions. Evidence of abuse of farmers via scale adjustment, under invoicing, cheating on bonus payment and the conditioning of farmers to mortgage their farms remain steadfast in their conviction that cocoa is critical to their livelihood and their positive attitudinal disposition towards the cocoa enterprise remains strong. This however cannot be taken for granted. Concerted and urgent action needs to be taken to protect farmers from those bent on milking them.